Formal enterprise modeling of batch plants using projects - Canavesio, Mercedes M. (2002)
Intense competition and rapid environmental changes are revealing severe limitations and drawbacks of the hierarchical and functional-oriented management system currently used by the vast majority of batch plants. In this work, a formal modeling framework for batch plants using projects and situation calculus is proposed. Projects are autonomous, temporary entities within the enterprise, in which different types of expertise are combined to achieve a concrete set of goals or deliverables. Situation calculus is used to represent the plethora of relationships involving projects, resources, actors etc. at different levels of abstraction over time. The use of a formal language permits to define the enterprise model specifications for rigorous reasoning about batch plant structure and behaviour. The proposed framework is exemplified with a case study comprising a dairy facility that involve the production 100+ different fresh products using an order-driven management system.